Well Begun but Not Yet Done : Progress and Emerging Challenges for Poverty Reduction in Vietnam - Kozel, Valerie (World Bank Group, Washington, DC, 2014)
This book presents the key findings from a new poverty assessment for Vietnam, led jointly by the World Bank and the Vietnam Academy of Social Sciences (VASS). It takes a fresh look at the lives of poor men, women, and children, and explores the constraints and opportunities they face today in rising out of poverty. The book aims to do three things. First, it proposes revisions to Vietnam’s poverty monitoring system—via better data, updated welfare aggregates, and new poverty lines—to bring these more in line with economic and social conditions in present-day Vietnam. Second, it revisits the stylized facts about deprivation and poverty in Vietnam, and develops an updated profile and diagnostic of poverty using data from the most recent Vietnam Household Living Standards Survey (VHLSS 2010), complemented by new qualitative field studies. Third, it aims to forge a consensus around some of the key challenges for reducing extreme poverty and promoting shared prosperity over the next decade, including changing regional patterns of poverty and wealth, high and persistent poverty among ethnic minorities, substantial and increasing vulnerability, and rising inequality in outcomes and opportunities.